Zoomorphic clay figurines from the Early Bronze Age settlement of Harich - Saribekyan, Mariam (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Harich is one of the Early Bronze Age archaeological sites of Armenia. The site is also known with its anthropomorphic and zoomorphic figurines dated to that period, the subject-matter of this article. These figurins that are now kept in the archaeological funds of the History Museum of Armenia could serve as an important group of artefacts that would help us to deepen our knowledge about the lifestyle and beliefs of the ancient population of that period.